Interactive design and gamification of eBooks for mobile and contextual learning - Bidarra, José (2015)
Given the global spread of mobile platforms like iOS and Android, it is relevant to consider the potential of these devices to teach and learn. Our exploratory research was designed to evaluate the possibility of using common eBook formats to create gamebooks (gamified books) that are effective in teaching and learning. After analyzing the features available in many free or open tools, we decided to use iBooks Author to build a model of a dynamic book that may function as an educational game for "Environmental Studies", aimed at children in the 4th grade, mostly 9 to 10- year olds enrolled in Portuguese schools. This paper pre- sents the design and features of this interactive book titled "Adventures in the Guadiana River", developed using the Apple iBook format, and especially set for the iPad retina. Because this is a proprietary format, we also built a proto- type following the EPUB3 standard and developed new ways to interact with content within this universal format. Preliminary tests with our prototypes revealed very good usability and a promising pedagogical potential for the proposed models.